STRUKTUR MODAL TERHADAP ECONOMIC VALUE ADDED PADA PT PRIMARINDO ASIA INFRASTRUCTURE TBK TAHUN 2001-2015 - Muthahhari, Muhammad Husain; Purnamasari, Imas; Sulastri, Sulastri (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - This study was conducted to look at the capital structure and economic value addedDesign / methodology / approach -The method of this research using and verification.. The object of this research is PT Primarindo Asia Infrastructure Tbk. Data collection techniques with time series. Data analysis techniques using multiple analysis techniques that is with the help of SPSS 20 for windows.Findings - Based on the results of research using verifikatif analysis, obtained the result that the capital structure does not have a positive effect on economic value added which means if there is a change in capital structure will affect with the increase of economic value addedOriginality / value - This research provides a basis for understanding the issues of capital structure overview and Economic value added. The difference of this research with the previous research is located on the object which is the company in the manufacturing industry that is PT Primarindo Asia Infrastructure Tbk with the variables studied are capital structure, and economic value added, and using theory or reference different from previous researchers. The results of this study that the structure of the capital in the nose using debt to equity ratio has a negative result